All My Life : A Memoir - Lucci, Susan; Morton, Laura 1964- (New York : !t Books, 2011)
The four-decade star of "All My Children" offers behind-the-scenes stories from the show and discusses the joys and heartaches of her life.
Introduction : The streak is over -- Born to perform -- Marymount College -- You're too ethnic-looking -- Hello, New York -- The early days of All my children -- Being Erica Kane -- Blended lives -- From All my children to all of my children -- Annie get your gun -- Life is a cabaret -- The cycle of life -- Celebrations -- That elusive Emmy -- The inner sanctum -- Dancing with the stars -- Africa -- Good bye, New York -- Looking back to go forward -- A fan letter to my fans -- My favorite things.
Keywords: Lucci, Susan; Actors -- Biography -- United States